2017
DOI: 10.29008/etc2017-267
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis on Turbocharger Radial Turbine with Heat Transfer

Abstract: Inconsistent results about heat transfer effects on performance and poor understanding of the aerothermodynamics loss mechanisms related to heat transfer in turbocharger turbine motivated this study. This study aimed to investigate the sensitivity of performance to heat loss and to quantify loss mechanisms associated with heat transfer in a turbine by using exergy analysis. A hybrid simulation methodology, i.e. Detached Eddy Simulation (DES) was used to compute the three-dimensional flow field of a turbine ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thermodynamic investigations of turbochargers are often carried out with energy balances, based on the first law of thermodynamics. However, conclusions offered by the authors of [12,13] clearly state that, from a thermodynamic point of view, the aerothermodynamic turbine behavior cannot be fully investigated merely using the first law of thermodynamics. Based on this research gap, further efforts, including exergy analysis, are needed to build a better thermodynamic view of heat transfer losses, one that considers the irreversibilities of every process.…”
Section: Experimental Exergy Analysis Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic investigations of turbochargers are often carried out with energy balances, based on the first law of thermodynamics. However, conclusions offered by the authors of [12,13] clearly state that, from a thermodynamic point of view, the aerothermodynamic turbine behavior cannot be fully investigated merely using the first law of thermodynamics. Based on this research gap, further efforts, including exergy analysis, are needed to build a better thermodynamic view of heat transfer losses, one that considers the irreversibilities of every process.…”
Section: Experimental Exergy Analysis Methodologymentioning
confidence: 99%
“…Furthermore, S. M. Lim et al concluded that the amount of losses caused by heat transfer and internal irreversibilities occurs during the expansion process and fluctuates between factors of 8 and 15 for different operating points. The total irreversibilities exceed the generated power by a substantial factor and, as a result, must not be neglected [12]. A. Diango et al have carried out an exergy analysis and optimization for the application of small turbomachines under non-adiabatic operations.…”
Section: Introductionmentioning
confidence: 99%